Peak width of skeletonized mean diffusivity in cerebral amyloid angiopathy: Spatial signature, cognitive, and neuroimaging associations - Zanon Zotin, Maria Clara; Schoemaker, Dorothee; Raposo, Nicolas; Perosa, Valentina; Bretzner, Martin; Sveikata, Lukas; Li, Qi; van Veluw, Susanne J.; Horn, Mitchell J.; Etherton, Mark R.; Charidimou, Andreas; Gurol, M. Edip; et al. (Frontiers in Neuroscience, 2022)
Background: Peak width of skeletonized mean diffusivity (PSMD) is a promising diffusion tensor imaging (DTI) marker that shows consistent and strong cognitive associations in the context of different cerebral small vessel diseases (cSVD). Purpose: Investigate whether PSMD 1) is higher in patients with Cerebral Amyloid Angiopathy (CAA) than those with arteriolosclerosis; 2) can capture the anteroposterior distribution of CAA-related abnormalities; 3) shows similar neuroimaging and cognitive associations in comparison to other classical DTI markers, such as average mean diffusivity (MD) and fractional anisotropy (FA). Methods: We analyzed cross-sectional neuroimaging and neuropsychological data from 90 non-demented memory-clinic subjects from a single center. Based on MRI findings, we classified them into probable-CAA (those that fulfilled the modified Boston criteria), subjects with MRI markers of cSVD not attributable to CAA (presumed arteriolosclerosis; cSVD), and subjects without evidence of cSVD on MRI (non-cSVD). We compared total and lobe-specific (frontal and occipital) DTI metrics values across the groups. We used linear regression models to investigate how PSMD, MD, and FA correlate with conventional neuroimaging markers of cSVD and cognitive scores in CAA. Results: PSMD was comparable in probable-CAA (median 4.06 x 10-4 mm2/s) and cSVD (4.07 x 10-4 mm2/s) patients, but higher than in non-cSVD (3.30 x 10-4 mm2/s; p<0.001) subjects. Occipital-frontal PSMD gradients were higher in probable-CAA patients, and we observed a significant interaction between diagnosis and region on PSMD values (F(2, 87) = 3.887, p = .024). PSMD was mainly associated with white matter hyperintensity volume, whereas MD and FA were also associated with other markers, especially with the burden of perivascular spaces. PSMD correlated with worse executive function (=-0.581, p<0.001) and processing speed (=-0.463, p=0.003), explaining more variance than other MRI markers. MD and FA were not associated with performance in any cognitive domain. Conclusions: PSMD is a promising biomarker of cognitive impairment in CAA that outperforms other conventional and DTI-based neuroimaging markers. Although global PSMD is similarly increased in different forms of cSVD, PSMD’s spatial variations could potentially provide insights into the predominant type of underlying microvascular pathology.